Cover, Content, and Editorial Note from Pengabdianmu J Pengabdian Masyarakat Vol. 7 No. 6 November 2022 - PengabdianMu J Pengabdian Masyarakat, Chief Editor of (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Assalamu’alaikum Wr. Wb. Now PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat re-published on Volume 7 Issue 6 November 2022. This edition marks a change in publication frequency from four to six times a year. The publication of PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat certainly participates in disseminating the results of community services in science and technology development conducted by lecturers and researchers, especially from UMPR and other universities. This edition contains 17 articles on Education, Social and Political, Agriculture, and Health Science topics. Editorial boards are fully aware that there is still room for improvement in this edition; hence with all humility, willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, can re-participate in the publication’s success in the next edition on January 2023. Wassalamu’alaikum Wr. Wb.